Potencial de dispersão de moluscos e macroinvertebrados de água doce por peixes neotropicais - Santin, Luciani Figueiredo (2016)
Mollusks can be a very frequent feeding item in the diet of many species of fishes inhabiting the Neotropical region. However, the possibility of malacofagous fishes act as important passive dispersors for native and exotic mollusks in rivers of this region is poorly documented. In this study, mollusks ability to survive of passing through the digestive system of Pimelodus pintado, Iheringichthys labrosus, Leporinus obtusidens and Rhinodoras dorbignyi, four species common in Southern Brazilian rivers, was evaluated. Three study methods, namely, intestinal content analysis, faecal content analysis and a laboratorial experiment, in which different mollusk taxa/morphotypes were offered to fishes, were used. Results obtained showed that the studied fish species apparently predate especially thinshelled morphotypes, although generally feeding on a variety of mollusk taxa/morphotypes. However, only thick-shelled morphotypes (Heleobia spp., Potamolithus spp., and Corbicula fluminea) were found alive in the fish rectum or feces. Individuals found alive not always survived more than 12 hours after having been placed on recipients containing water and oxygen. This result suggests that other factors should be involved in mollusks ability to survive. The absence of strong incisiform oral teeth in fish digestive tract is important for the survival of many mollusks, because their presence, such as in L. obtusidens, determinate the fragmentation of many shells. Thus, only P. pintado, I. labrosus and R. dorbignyi, which do not show this tooth type, could be considered as passive dispersers of some mollusk taxa, and of some Hidropsyche larvae and leeches in rivers of the Neotropical region. Possibly, these fish species were also involved in the invasion of many non-navigable streams in southern Brazil, by the Asiatic bivalve C. fluminea.